Prevalence and Incidence of HIV Infection among Fishermen along Lake Victoria Beaches in Kisumu County, Kenya - Ondondo, Raphael O.; Ng’ang’a, Zipporah W.; Mpoke, Solomon; Kiptoo, Michael; Bukusi, Elizabeth A. (Scientific Research, 2014)
Background: Herpes simplex virus type-2 (HSV-2) and human papillomavirus (HPV) are common sexually transmitted infections (STIs) among fishing communities and are associated with high HIV prevalence in this underserved population. However, there is limited knowledge on HIV incidence among fishermen. This study aimed at determining prevalence, incidence and risk factors associated with HIV infection among fishermen in Kisumu Kenya. Methods: Three hundred fishermen were evaluated for baseline HIV, HSV-2, HPV infection and a structured questionnaire administered. HIV incidence was assessed after 12 months among those initially HIV negative. HIV incidence rate in person-years and prevalence were estimated. Multivariate logistic regression was used to determine factors independently associated with HIV acquisition. Results: HIV prevalence was 23.3% (95% CI: 18.5 - 28.1). Risk factors for baseline HIV prevalence were older age (aOR = 2.13; 95% CI: 1.25 - 5.07), history of STI (aOR 4.21; 95% CI: 2.07 - 9.34), baseline HPV infection (aOR 2.13; 95% CI: 1.05 - 4.77), number of lifetime sexual partners (>5) aOR = 5.76 (95% CI: 1.41 - 13.57) and transactional sex (aOR = 10.98; 95% CI: 1.86 - 19.34). Condom uses with new sexual partner (aOR 0.21, 95% CI: 0.08 - 0.55) and during most recent sexual act (aOR 0.09, 95% CI: 0.03 - 0.61), were negatively associated with HIV prevalence. HIV incidence was 4.2 (95% CI = 1.3 - 7.1) per 100 person-years with being single (aIRR = 8.32; 95% CI: 1.27 - 54.67) as an independent risk factor. Condom use with new sexual partner (aIRR = 0.11; 95% CI: 0.01 - 0.89) and recent sex with wife/regular girlfriend (compared to sex worker/casual partner; aIRR = 0.03; 95% CI: 0.01 - 0.35) were associated with reduced risk of HIV acquisition. Conclusion: Inconsistent condom use and transactional/casual sexual partnerships were the main high-risk sexual behaviors in addition to marital status explaining the high HIV acquisition rate among fishermen. Intensified safer sex promotion is urgently needed in this subpopulation to avert new HIV infections.
Keywords: HIV; Incidence; Prevalence; Fishermen; Sexual Behavior